Avaliação do conforto térmico de um escritório localizado no município de Tucuruí/PA com base na norma ABNT NBR 16401-2 - COSTA, Thiago Barroso (2021)
Thermal comfort is a necessary condition for the human being to be in a total state of wellbeing. Since, under thermal discomfort, the individual compromises his performance in any task he tries to perform. Therefore, it becomes common to apply air conditioning systems in occuped environments, in order to adapt them to thermal comfort conditions. However, an oversized air cooling system and/or without adequate control, can cause cold sensations to the occupants of the environment. Based on that, this study is dedicated to assessing the conditions of thermal comfort inside an air-conditioned enclosure. In which the users are practicing sedentary activities typical of an office, do not take control of the system, and eventually report discomfort due to the feeling of cold. To assess the thermal comfort of that room, the methods recommended by the ABNT NBR 16401-2 (2008) standard were applied, i.e., the determination of the PMV/PPD indices, Comfort Zones, and the analysis of Local Discomfort. Thereby, it was verified analytically that, in fact, the environment presented situations of general thermal discomfort and local discomfort due to the sensation of cold. In addition, the condition of thermal discomfort during the analyzed period worsened over time, especially at dusk. Thus, it was concluded that the employees need to be more active in changing the system's setpoint to adapt it to specific occasions, especially at night, when there is a greater decrease in the internal operative temperature of the environment.